(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Evaluating the initial results of anesthesia for pediatric liver transplantation at Children Hospital 2: the results achieved and the problems still exist. Designe: Conducting anesthesia in pediatric liver transplant surgery in three phrases from 2005-2019, 2021-2022 and 2023-2025. From the support of anesthesiologists from Belgium in the early stage to autonomy in anethesia. Results: From December 2005 to June 2025 we performed general anesthesia in pediatric liver transplant surgeries in 54 patients having end-stage liver disease (ESLD), with 52 living donnors and 2 deceased donnors. Patient age from 7,5 to 132 months old in young female than male (29/25), and average weight 11,5kg (6,8-27 kg); With 47 patients had biliary atresia, 1 Alagille syndrome, 2 Budd Chiari syndromes and 4 PFIC. There were 7 cases having hepatopulmonary syndromes, 2 had pulmonary hypertension and 1 had hepatic encephalopathy. All of them had trouble of hemostasis that 10 patients were massive blood transfusions. The average duration of anesthesia was 11hours 25 minutes (08:30-13:20). Extubation were performed in the 1st or 2nd postoperative day. Conclusion: Anesthetic management was contributing to the initial success of pediatric liver transplantation from living donor at Children Hospital 2. To ensure more safety for patients, it’s necessary to profoundly understand of the physiological and metabolic changes in ESLD. Remarkable changes during operation should be managed. Close communication between surgical team and the anesthesiologists is the most important issue in patient management.